Dinamika Pengembangan SDM, Iklim Organisasi, Transparansi Kinerja, dan Disiplin Integratif dalam Memperkuat Reformasi Birokrasi Polri - Laoli, Elvianus; Kristianingsih, Ekawaty (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Bureaucratic reform within the Indonesian National Police (Polri) is a crucial agenda aimed at building a professional, accountable, and adaptive law enforcement institution. However, the success of this reform is not solely determined by structural changes, but also by internal dynamics involving human resource (HR) development, organizational climate, performance transparency, and integrative discipline. This study aims to analyze the interplay of these four dimensions in strengthening the implementation of Polri’s bureaucratic reform. Using a qualitative approach through a literature review, this research critically examines academic journal articles, institutional policies, and relevant studies published within the past ten years. The findings indicate that competency-based HR development plays a significant role in enhancing professional capacity among police personnel. A supportive organizational climate fosters collaboration, open communication, and trust within the institution. Performance transparency reinforces public accountability and reduces opportunities for misconduct, while integrative discipline ensures consistent ethical behavior as the foundation of institutional integrity. The synthesis of literature reveals that Polri’s bureaucratic reform can only be effective when these four factors are managed simultaneously and integrated cohesively. This study contributes theoretically to the field of police management and provides practical recommendations for strengthening governance within the Polri Presisi reform framework.